Forensic Frontiers: Unraveling Leading Trends in Digital Investigations - Eka Safitri, Annisa; Tanzil Multazam, Mochammad (International Consortium of Education and Culture Research Studies, 2023)
In this study, researchers analysed scientific journal articles in the field of digital forensics and law through the Lens.org website. The purpose of this study is to find the best universities, years, fields of study, authors, countries/regions, publishers, and journals in this field. The method used was to filter journal articles based on document type, data range, and field of study. The study results show that the University of Lausanne is the best institution in this field, 2021 is the year of the most journals, the field of computer security is the best field of study, the Netherlands Forensic Institute is the most active institution, Eoghan Casey is the most active author, the United Kingdom is the most active country/region, and Elsevier is the best publisher. The scientific impact of this study is to provide an overview of the best journal articles in the field of digital forensics and law, so that it can help researchers or practitioners in choosing quality information sources. Highlights: Institutional prowess: Highlighting the University of Lausanne and the Netherlands Forensic Institute emphasizes their significance in advancing digital forensic research within the legal domain. Focused insights: The study narrows down to the peak year, top field of study, and most active author, providing precise insights for researchers seeking targeted information. Publisher prominence: Identifying Elsevier as the leading publisher emphasizes their role in disseminating crucial research in this specialized field. Keywords: Digital Forensics, Law, Scholarly Journals, Benchmarking, Key Contributors